2011
DOI: 10.3390/polym3031051
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diblock Copolymer Consisting of Poly(4-butyltriphenylamine) and Morphological Control in Photovoltaic Application

Abstract: Abstract:The diblock copolymer PTPA-b-PS consisting of poly(4-butyltripheneylamine) (PTPA) and polystyrene was prepared by atom transfer radical polymerization followed by C-N coupling polymerization. Three types of block copolymers with different contents of polystyrene segment were prepared. The formation of block copolymer was confirmed by 1 H NMR spectra and gel permeation chromatography (GPC) profiles. Time of flight (TOF) measurement revealed that the block copolymer showed higher hole mobility up to 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…As a result, PBTPA-b-poly(ethylene oxide) [9] and PB-TPA-b-polystyrene [11] were synthesized using polymer modified aryl bromides as terminal modifiers. However, preliminary studies revealed that the preparation of PB-TPA-b-PBA via C-N coupling polymerization in the presence of a terminal modifier with PBA chain or ATRP initiating 2-bromopropionate moiety afforded PBTPA homopolymer without designed chain end in a relatively low yield.…”
Section: Synthesis Of Pbtpa-tbs Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, PBTPA-b-poly(ethylene oxide) [9] and PB-TPA-b-polystyrene [11] were synthesized using polymer modified aryl bromides as terminal modifiers. However, preliminary studies revealed that the preparation of PB-TPA-b-PBA via C-N coupling polymerization in the presence of a terminal modifier with PBA chain or ATRP initiating 2-bromopropionate moiety afforded PBTPA homopolymer without designed chain end in a relatively low yield.…”
Section: Synthesis Of Pbtpa-tbs Precursorsmentioning
confidence: 99%
“…Recently, our group have. reported a new approach to synthesize PTAA from A-B type monomer by C-N coupling polymerization using palladium based system as a catalyst [9][10][11]. A serious of PTAA-based block copolymers have been successfully prepared by adding terminal modifying macroinitiators during the polymerizations.…”
Section: Introductionmentioning
confidence: 99%
“…A research group synthesized C 60 ‐functionalized polystyrene and used it as a replacement of C 60 in polymer solar cells . The effect of poly(4‐butyltripheneylamine)‐ block ‐polystyrene block copolymers on morphology and performance progress was also studied …”
Section: Introductionmentioning
confidence: 99%
“…Palladium catalyzed C-N coupling reaction is also applied to prepare PAA and block copolymers consisting of PAA block from A-B type monomer [5] [6]. PAAs are also promising materials for photovoltaic [7], and photorefractive [8] [9] applications.…”
Section: Introductionmentioning
confidence: 99%